Feasibility of quality indicators on prehospital advanced airway management in a physician-staffed emergency medical service: survey-based assessment of the provider point of view - Thomas Riva; Andreas Krüger; Stephen Johan Mikal Sollid; Mathieu Pasquier; Pierre-Nicolas Carron; David Caillet-Bois; Alexandre Kottmann; Ludovic Maudet; Jean-Daniel Rouvé; L Suppan; Roland Albrecht (BMJ Open)
Objective We aimed to determine the feasibility of quality indicators (QIs) for prehospital advanced airway management (PAAM) from a provider point of view.Design The study is a survey based feasibility assessment following field testing of QIs for PAAM.Setting The study was performed in two physician staffed emergency medical services in Switzerland.Participants 42 of the 44 emergency physicians who completed at least one case report form (CRF) dedicated to the collection of the QIs on PAAM between 1 January 2019 and 31 December 2021 participated in the study.Intervention The data required to calculate the 17 QIs was systematically collected through a dedicated electronic CRF.Primary and secondary outcome measures Primary outcomes were provider-related feasibility criteria: relevance and acceptance of the QIs, as well as reliability of the data collection. Secondary outcomes were effort to collect specific data and to complete the CRF.Results Over the study period, 470 CRFs were completed, with a median of 11 per physician (IQR 4–17; range 1–48). The median time to complete the CRF was 7 min (IQR 3–16) and was considered reasonable by 95% of the physicians. Overall, 75% of the physicians assessed the set of QIs to be relevant, and 74% accepted that the set of QIs assessed the quality of PAAM. The reliability of data collection was rated as good or excellent for each of the 17 QIs, with the lowest rated for the following 3 QIs: duration of preoxygenation, duration of laryngoscopy and occurrence of desaturation during laryngoscopy.Conclusions Collection of QIs on PAAM appears feasible. Electronic medical records and technological solutions facilitating automatic collection of vital parameters and timing during the procedure could improve the reliability of data collection for some QIs. Studies in other services are needed to determine the external validity of our results.